The first thing you need to do is to get all of the terms with numbers on one side of the equation and your variable term on the other. By doing this, you add your fraction (1/6) to both sides of the equation. Now you have

2m = 3 1/6

Now what you have to do is divide both sides by 2 to solve for m. That gives you

m = (3 1/6) / 2

3 1/6 is 19/6. If you divide that by 2 you get

9.5/6

So

m = 9.5/6

2m-1/6 = 3 is an equation .

m is the unknown.

This could be solved for m.

2m-1/6 = 3. Add 1/6 .

2m = 3+1/6

2m = 19/6. Divide by 2.

m = 19/12.

Supposing that you want to find out the value of m, we'll solve the equation in m in this way:

2m - 1/6 = 3

We'll isolate 2m to the left side. For this reason, we'll add 1/6 both sides:

2m - 1/6 + 1/6 = 3 + 1/6

We'll eliminate like terms from the left side, namely 1/6 and -1/6:

2m = 3 + 1/6

We'll multiply 3 by 6:

2m = (3*6 + 1)/6

2m = 19/6

We'll divide by 2:

m= 19/6*2

**m = 19/12**

If the equation is (2m - 1)/6 = 3,we'll cross multiply and we'll get:

2m - 1 = 6*3

2m - 1 = 18

We'll add 1 both sides:

2m = 18+1

2m = 19

We'll divide by 2 both sides:

m = 19/2

**m = 9.5**

**So, the conclusion is: It's important to write correctly an equation that contains quotients.**